1963
DOI: 10.1001/archpedi.1963.02080050103017
|View full text |Cite
|
Sign up to set email alerts
|

Sequelae of Premature Birth

Abstract: where and transferred to the Premature Infant Center. During this time, a total of 187 infants were admitted of whom 87 died in the neonatal period while 6 succumbed in the subsequent 11 months. The 94 who survived the first year of life constituted the sample to be followed.The examination included medical and neurologi¬ cal examinations, psychological testing, electroencephalography, ophthalmological examination, and evaluation of the social situation of the families of the patients. The children returned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

1965
1965
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(30 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…After delivery, the preterm infant was placed in an incubator with liberal amounts of oxygen and if still alive 2-3 days later, feedings were begun (frequent aspiration had discouraged earlier feeding) [Gordon, 1952]. Hyperoxia contributed to ROP in a third and blindness in 20% of survivors, while delayed feeding contributed to major disability in half [Drillien, 1961;Lubchenco et al, 1963;1972;Francis-Williams and Davies, 1974]. Antibiotics available to treat infections had unfortunate side effects in preterm infants, including hearing impairment with streptomycin, hyperbilirubinemia due to albumin binding with sulfonamides and "gray baby syndrome" (i.e., shock) with chloramphenicol.…”
Section: Historical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…After delivery, the preterm infant was placed in an incubator with liberal amounts of oxygen and if still alive 2-3 days later, feedings were begun (frequent aspiration had discouraged earlier feeding) [Gordon, 1952]. Hyperoxia contributed to ROP in a third and blindness in 20% of survivors, while delayed feeding contributed to major disability in half [Drillien, 1961;Lubchenco et al, 1963;1972;Francis-Williams and Davies, 1974]. Antibiotics available to treat infections had unfortunate side effects in preterm infants, including hearing impairment with streptomycin, hyperbilirubinemia due to albumin binding with sulfonamides and "gray baby syndrome" (i.e., shock) with chloramphenicol.…”
Section: Historical Perspectivementioning
confidence: 99%
“…Rates of neurological and intellectual abnormalities increased as BW decreased in a longitudinal study comparing 500 low birthweight infants (LBW, with BW below 2500 grams) born in 1952 in Baltimore MD to 492 fullterm controls matched for SES and race [Knoblach et al, 1956;Wiener et al, 1968]. Over half of very low birthweight children (VLBW, with BW below 1500 grams) had major disability and required special education, and three quarters had behavior problems [Knoblach et al, 1956;Drillien, 1961;Lubchenco et al, 1963]. Although samples of preterm children demonstrated a normal range of intelligence, many more (46-69%) had low intelligence quotients (IQ below 90) than fullterm controls (8-9%).…”
Section: Historical Perspectivementioning
confidence: 99%
“…In fact, many studies are available to show that babies "born too soon or born too small" (46) are at a high risk for developing behavioral disorders, particularly hyperactivity and learning disabilities (41)(42)(43)(44)(45)(105)(106)(107)(108)(109), with boys displaying this syndrome more often than girls (46). Since only a small proportion of the high-risk children are diagnosed as suffering from behavioral abnormalities, and some of the potential disorders may be prevented by special care, it may be advisable to screen those at risk for the presence of retarded brain development and its extent by using the magnetic resonance imaging technique.…”
Section: Morphological and Behavioral Markers Of Retarded Brain Develmentioning
confidence: 99%
“…In a retrospective study, Pasamanick and Knobloch (36) found that a higher proportion of children with school problems than matched control children had perinatal medical complications, and that their major symptom was hyperactivity. Several large-scale recent studies have established that prematurely born babies and small-for-date babies are at a high risk for developing hyperactivity and/or learning disabilities (41)(42)(43)(44)(45)(46).…”
mentioning
confidence: 99%
“…Mortality rate and long-term out come were discouraging [1][2][3][4][5]. During recent years considerable improvement in the sur vival rate and short-and long-term outcome of these tiny infants has been reported [6][7][8][9][10], as a result of improved antenatal fetal and maternal monitoring, an increased tendency to perform operative deliveries for fetal indi cations, and of considerable improvement in neonatal intensive care [8,11].…”
Section: Introductionmentioning
confidence: 99%